Inner cannula aspiration in a laryngectomized patient: a case report - Hırçın, Zafer; Eskiizmir, Görkem (ENT Updates, 2013)
In laryngectomized patients, foreign body aspiration into the tracheobronchial system is an emergency condition and may cause acute respiratory distress; although it is very rare. In this case report, symptomatology, diagnostic evaluation and treatment modality of a laryngectomized patient who had inner cannula aspiration into the tracheobronchial system were presented.